2009
DOI: 10.1080/02652030802366090
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin B2production byAspergillus nigerin Thai coffee beans

Abstract: During 2006 and 2007, a total of 64 Thai dried coffee bean samples (Coffea arabica) from two growing sites in Chiangmai Province and 32 Thai dried coffee bean samples (Coffea canephora) from two growing sites in Chumporn Province, Thailand, were collected and assessed for fumonisin contamination by black Aspergilli. No Fusarium species known to produce fumonisin were detected, but black Aspergilli had high incidences on both Arabica and Robusta Thai coffee beans. Liquid chromatography (LC) with high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 24 publications
7
74
1
1
Order By: Relevance
“…Previous studies indicate that about two-third of A. niger/A. awamori isolates are able to produce fumonisins (Noonim et al 2009;Logrieco et al 2009;Mogensen et al 2010;Varga et al 2010). Interestingly, the amount of 3-epi-FB 4 exceeded the amount of FB 4 in sample A, although in our previous investigations we found that the amount of FB 4 exceeded that of 3-epi-FB 4 in all raisin samples ).…”
Section: Fumonisin Contamination Of Onion Samplescontrasting
confidence: 52%
See 1 more Smart Citation
“…Previous studies indicate that about two-third of A. niger/A. awamori isolates are able to produce fumonisins (Noonim et al 2009;Logrieco et al 2009;Mogensen et al 2010;Varga et al 2010). Interestingly, the amount of 3-epi-FB 4 exceeded the amount of FB 4 in sample A, although in our previous investigations we found that the amount of FB 4 exceeded that of 3-epi-FB 4 in all raisin samples ).…”
Section: Fumonisin Contamination Of Onion Samplescontrasting
confidence: 52%
“…Recent data indicate that sequence-based methods can be used successfully for species assignment in this group of organisms . Such an approach is important since some members of section Nigri are 4 mycotoxin producers and are able to contaminate several food products with ochratoxins and/or fumonisins Frisvad et al 2007;Varga and Kozakiewicz 2006;Noonim et al 2009;Varga et al 2010). To our knowledge, black Aspergilli infecting onion bulbs have not yet been reliably identified to species level using a sequencebased approach.…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium verticillioides and Fusarium proliferatum (Rheeder et al 2002). Recently, fumonisins B 2 and B 4 (FB 2 , FB 4 ) were also detected in Aspergillus niger (Frisvad et al 2007b;Noonim et al 2009) and Tolypocladium (Mogensen et al 2010a). Fumonisin production has also been detected in a single strain of Alternaria arborescens (as Alternaria alternata f. sp.…”
mentioning
confidence: 99%
“…Moreover, Aspergillus niger can produce ochratoxin A and fumonisin B2 and aflatoxins [20,1]. A plant that is known as a strong antifungal medical plant is Mentha spicata L. (Spearmint).…”
Section: Introductionmentioning
confidence: 99%